Hepatitis E virus is effectively inactivated by methylene blue plus light treatment. Issue 11 (20th September 2022) - Gravemann, Ute; Engelmann, Michael; Kinast, Volker; Burkard, Thomas; Behrendt, Patrick; Schulze, Torsten J.; Todt, Daniel; Steinmann, Eike
Abstract: Background and objectives: Photodynamic treatment with methylene blue (MB) and visible light is a well‐established pathogen inactivation system for human plasma. This technique is routinely used in different countries. MB/light treatment was shown to inactivate several transfusion‐transmittable viruses, but its efficiency for the inactivation of the quasi‐enveloped hepatitis E virus (HEV) has not yet been investigated. Materials and methods: Plasma units were spiked with cell culture‐derived HEV and treated with the THERAFLEX MB‐Plasma system using various light doses (30, 60, 90, and 120 J/cm 2 ). HEV titers in pre‐ and post‐treatment samples were determined by virus titration and a large‐volume plating assay to improve the detection limit of the virus assay. Results: THERAFLEX MB‐Plasma efficiently inactivated HEV in human plasma. Even the lowest light dose of 30 J/cm 2 inactivated HEV down to the limit of detection, with a mean log reduction factor of greater than 2.4 for the total process. Conclusion: Our study demonstrates that the THERAFLEX MB‐Plasma system effectively inactivates HEV in human plasma.